North by Southwest: Screening the Naturally Isolated Microalgal Strains from Different Habitats of Iran for Various Pharmaceutical and Biotechnology Applications. (12th August 2022) - Dinpazhooh, Zahra; Niknezhad, Seyyed Vahid; Fadaei, Fardin; Shaker, Saeedeh; Najafpour, Ghasem; Ghasemi, Younes; Mousavi, Pegah; Morowvat, Mohammad Hossein
Abstract : Background and Aims . Microalgae are known as a promising source for food, pharmaceutical, and biofuel production while providing environmental advantages. The present study evaluates some newly isolated microalgal strains from north and southwest of Iran as a potential source for high-value products. Methods . Primitive screening was carried out regarding growth parameters. The molecular and morphological identifications of the selected strains were performed using 18S rRNA gene sequencing. After phylogenic and evolutionary studies, the selected microalgal strains were characterized in terms of protein and pigment content, in addition to the fatty acid profile content. Besides, the CO2 fixation rate was determined to assess capability for various environmental applications. Results . All of the selected strains were predominantly belonging to Scenedesmus sp. and Desmodesmus sp. The isolated Scenedesmus sp. VN 009 possessed the highest productivity content and CO2 fixation rate of 0.054 g·L −1 d −1 and 0.1 g·L −1 d −1, respectively. Moreover, data from GC/MS analysis demonstrated the high robustness of this strain to produce several valuable fatty acids including α -linolenic acid and linoleic acid in 45% and 20% of total fatty acids. Conclusions . The identified strains have a great but different potential for SCP, β -carotene, and ω -3 production, as well as CO2 fixation for environmental purposes. In this study, considering the wide range of microalgal strains in different habitats of Iran, the potential applications of native microalgae for various pharmaceutical, food, and biotechnology purposes were investigated.